The TA'AWUN Model for Digital Library Management in Indonesian Islamic Boarding Schools - Syarijuddin Al Farisi; Badrudin; Yana Aditia Gerhana; Dewi Sadiah (Women, Education, and Social Welfare, 2026)
Indonesian Islamic boarding schools (pesantren) must expand access to classical Islamic texts while safeguarding the chain of scholarly transmission (sanad) and etiquette toward knowledge (adab). This study developed and descriptively evaluated the TA'AWUN digital library management model through a mixed-methods Research and Development design using the Analysis, Design, Development, Implementation, and Evaluation framework. The study was conducted at Pondok Pesantren Daarul Haliim, West Bandung Regency, Indonesia. The stakeholder pool comprised one Islamic boarding school leader (kyai), two library managers, five Islamic teachers (ustadz), thirty boarding-school students (santri), and three alumni; fifteen informants contributed qualitative data, while thirty-seven participants completed quantitative measures. Expert appraisal increased from 90.00% before revision to 98.33% after revision, and the limited trial produced a practicality score of 3.76/4.00. During the one-month implementation, mean compliance with six standard operating procedures reached 92.3%. Twenty of twenty-five targeted classical Islamic books (kitab kuning) were digitized, and all received documented sanad verification. Santri digital literacy scores increased descriptively from 62.5 to 78.2 (N-Gain = 0.42). User satisfaction reached 3.54 among santri and 3.83 among ustadz, while overall technology acceptance was 3.78/4.00. These findings provide preliminary, context-specific evidence that value-responsive digitalization can improve access and operational consistency without displacing pesantren epistemic traditions. Multi-site and longitudinal evaluation is required before broader effectiveness claims are made.